KARAKTERISTIK DINAMIKA STRUKTUR SATELIT MIKRO LAPAN-TUBSAT - Triharjanto, Robertus Heru; Sugiarmadji HPS (Indonesian Journal of Aerospace, 2005)
The TUBSAT-LAPAN micro satellite is planned to be launched using PSLV rocket. The design constraints of the mechanical system of the satellite are able to accomodate structural requirment for PSLV, which are first resonance frequency in the rocket longitudinal axis 90 Hz and first resonance frequency in the lateral axis 45 Hz. Therefore, the structural dynamic characteristic data of the satellite is important to be evaluated, such as natural frequency and mode shapes of the satellite structures, The normal modes analysis made is done usingh Finite Element Methods commercial software NASTRAN. To simplify the FEM modeling the satellite components inside the compartmens is replaced by a dummy load simulating their contribution to satellite mass, centerof gravity and inertia, which was made by the same material as the satellite's structure, i.e. Al-Alloy 2024T351. Meanwhile, the FEM modeling for both the UHF antena used the Stainless Steel materials as the real antena. The analysis results show that the lowest local natural frequency of the satellite occurs on the UHF antena. The first natural frequency of the antena structures in lateral direction is 52,29 Hz. The first natural frequency of the satellite in lateral direction 151.47 Hz completing the satellite integration, vibration test was done to the satellite. The test shows that the first global frequency is 72-75 Hz in the lateral direction and 148 Hz in longitudinal direction. Structural dynamic characteristic of TUBSAT_LAPAN micro satellite in free flying condition are also analyzed using no-constraint condition to check the safe separation clearance scenario. The results show that the first natural frequencies for satellite structures (combination) become very small, less than 0.00032 Hz. But, the lowest of the first natural frequency for UHF antena structures is almost constant, 52.30 Hz in lateral direction.